2014
DOI: 10.1681/asn.2013030225
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mTORC1 in Collecting Ducts Causes Hyperkalemia

Abstract: Mutation of TSC (encoding tuberous sclerosis complex protein) and activation of mammalian target of rapamycin (mTOR) have been implicated in the pathogenesis of several renal diseases, such as diabetic nephropathy and polycystic kidney disease. However, the role of mTOR in renal potassium excretion and hyperkalemia is not known. We showed that mice with collecting-duct (CD)-specific ablation of TSC1 (CDTsc1KO) had greater mTOR complex 1 (mTORC1) activation in the CD and demonstrated features of pseudohypoaldos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Recent studies have suggested a role for mTOR signaling in tubular Na + and K + handling (20,25,26,39). Genetic deletion of TSC1 (which encodes tuberous sclerosis complex protein 1), with ensuing constitutive activation of mTORC1 in CDs, was associated with hyperkalemia (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a role for mTOR signaling in tubular Na + and K + handling (20,25,26,39). Genetic deletion of TSC1 (which encodes tuberous sclerosis complex protein 1), with ensuing constitutive activation of mTORC1 in CDs, was associated with hyperkalemia (39).…”
Section: Discussionmentioning
confidence: 99%
“…Given these interactions between mTORC1 activity and cystogenesis, it is surprising that murine Tsc models are born with normal kidneys that later develop cysts with age. Investigations of both Tsc1 or Tsc2‐ associated renal cystic disease in the mouse directly (Armour, Carson, & Ess, ; Onda, Lueck, Marks, Warren, & Kwiatkowski, ; Zhou, Brugarolas, & Parada, ) or indirectly (Chen et al, ) demonstrate that cystogenesis is attributable to specific nephron segments, and all tubular segments have been implicated in murine Tsc cyst formation (Traykova‐Brauch et al, ). While all tubule segments probably could participate in cystogenesis, none of the published studies used a comprehensive panel of tubular segment markers to identify the cells involved.…”
Section: Cell Biology Of Tsc Renal Diseasementioning
confidence: 99%
“…) or indirectly (Chen et al. ) demonstrated that cystogenesis is attributable to specific nephron segments, and all tubular segments have been implicated in Tsc cyst formation (Traykova‐Brauch et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…One such model has been reported to be associated with a potassium excretion defect (Chen et al. ). Early investigation revealed that the majority of renal cysts maintain their Tsc locus integrity (Onda et al.…”
Section: Introductionmentioning
confidence: 99%